A PRELIMINARY REPORT ON THE NATURAL LEPTOMONAD INFECTION OF PHLEBOTOMUS MAJORIN AN ENDEMIC FOCUS OF VISCERAL LEISHMANIASIS (VL) IN FARS PROVINCE, SOUTH OF IRAN - Z. Sahabi; M. A. Seyedi Rashti; A. Nadim; E. Javadian; M. Kazemeini; M. R. ABAI (Tehran University of Medical Sciences, 1992)
In order to determine the vector of visceral leishmaniasis in the endemic focus of Fars Province in southern Iran, collection and dissection of sand- flies were carried out in the town of Ghjr in Firooz - abad district. A total of 270 sand- flies were dissected. They consisted of Ph. Alexandri, Ph. sergenti Ph. papatasi and Ph. major. Five out of 150 Ph. major was found infected with promastigotes three of them with the parasites in the gut as well as the head. This is the first report about the probable vector of kala - azar in Iran.